An Action Research: Improving Eleventh Grade Students’ Ability in Comprehending Report Text Through Skimming and Scanning Technique at SMAN 2 Tebo - Eka Andriyani (Cahaya Ilmu Cendekia Publisher, 2021)
Purpose of the study: The aim of this research is to improve reading comprehension of eleventh grade studentsof SMAN 2 Tebo on report text through Skimming and Scanning technique. Methodology: This study employed classroom action research design. In the study, the researcher collaborated with the English teacher who taught the target class. The subject of the research was eleventh grade students of IPA 1 class in SMAN 2 Tebo that consisted of 32 students. Main Findings: The result of the three cycles show that the use skimming and scanning technique was effective to improve the students’ reading comprehension on report text. Based on the reading test scores the students’ scores kept improving in every test. In cycle I test the mean was 67.50, in cycle II test the mean was 76.87 and in cycle III test the mean was 85.78. Novelty/Originality of this study: The improvement of students’ activeness and participation in the class were also seen from observation sheet and field note in implementing skimming and scanning when reading the texts in the classroom. The result of the research showed that Skimming and Scanning significantly improved students’ achievement in reading report text, particularly for eleventh grade students of IPA 1 class in SMAN 2 Tebo.